The productive and symbolic functions of internal control in the Chinese hotel industry - Wang, J; Hooper, K; Sinclair, RMS (The Department of Accounting and Finance, Unitec Institute of Technology, 2013)
The paper considers how mechanisms of internal control drawn from accounting concepts serve the “productive” and “symbolic” functions identified by Foucault (Foucault, 1980, p. 161) that are employed to control staff by hotel management. The approach is ethnographic, drawing on the experiences of the author who worked for several years in various Chinese hotels. The findings of the paper show the controls used to measure the productive and symbolic functions of staff performance. However, the symbolic function is of the increasing importance in the hotel industry and requires that staff become, in Foucauldian terms, efficient disciplined bodies.